Purification and characterization of embryo-specific soy urease (Glycine max) and its antifungal potential against Paracoccidioides brasiliensis - Ângelo, Elisângela Andrade; da Cruz, Tainá Michelle; Pattaro Júnior, José Renato; Zanzarin, Daniele Maria; Rodrigues, Franciele Abigail Vilugron; Pilau, Eduardo Jorge; Kioshima, Érika Seki; Fernandez, Maria Aparecida; Seixas, Flavio Augusto Vicente (Eclética Química, 2021)
Ureases are amidohydrolases that catalyze the hydrolysis of urea to ammonia and carbamate. In addition to the enzymatic function, ureases have fungitoxic and insecticidal function, which are independent of their catalytic activity. Soy (Glycine max) has two main urease isoforms: ubiquitous and embryo-specific, the latter is present in beans. In view of the potential applications of ureases, this work aimed to extract, purify, characterize the structure, activity and fungitoxic activity of soy urease against Paracoccidioides brasiliensis. The biochemical characterization was performed, in terms of optimal pH and temperature, as well as the determination of the Michaelis–Menten constant (KM) and maximum velocity (Vmax). The protein sequence was identified by mass spectrometry and used in computational modeling of the biological structure. The optimum pH and temperature of the enzyme were 6.5 and 65 °C, respectively, KM 526 mmol L-1 and Vmax 7.4 mmol L-1 NH3×µgurease-1×s-1 and biological unity as a trimer. The antifungal activity assays (in vitro) were promising, showing a fungicidal profile of the urease, with a minimum inhibitory concentration of 10 µg×mL-1. This work demonstrated, for the first time, the fungitoxic activity of embryo-specific soy urease against the Pb18 strain of P. brasiliensis.